Trends in epidemiology and outcomes of respiratory distress syndrome in the United States. Issue 4 (20th January 2019) - Donda, Keyur; Vijayakanthi, Nandini; Dapaah‐Siakwan, Fredrick; Bhatt, Parth; Rastogi, Deepa; Rastogi, Shantanu
Abstract: Background: The management practices of Respiratory Distress Syndrome (RDS) in the newborn have changed over time. We examine the trends in the epidemiology, resource utilization, and outcomes (mortality and bronchopulmonary dysplasia [BPD]) of RDS in preterm neonates ≤34 weeks gestational age (GA) in the United States. Methods: In this retrospective serial cross‐sectional study, we used ICD‐9 codes to classify preterm infants GA ≤34 weeks between 2003 and 2014 from the National Inpatient Sample as having RDS or not. Trends in the prevalence of infants defined as RDS by ICD‐9 code (ICD9‐RDS), length of stay, BPD, and mortality were analyzed using Cochran‐Armitage and Jonckheere‐Terpstra tests and multivariable logistic regression. Results: Of 1 526 186 preterm live births with GA ≤34 weeks, 554 409 had ICD9‐RDS (260 cases per 1000 live births) with the prevalence increasing from 170 to 361 ( P trend  < 0.001) and associated decrease in all‐cause mortality (7.6% to 6.1%; P trend  < 0.001) from 2003 to 2014. Increased utilization of non‐invasive mechanical ventilation (NIMV) (69.5% to 74.3%; P trend  < 0.001) was associated with decreased invasive mechanical ventilation (IMV) use >96 h (60.4 to 56.6%; P trend  < 0.001). Exclusive NIMV use increased from 16.8% to 29.1% ( P trend  < 0.0001). BPD incidence decreased from 14% to 12.5% ( P trend  < 0.001). LOS increased from 32 days to 38 days ( P trend  < 0.001) and cost increased from $49, 521 to $55, 394 ( P trend  < 0.001). Conclusion: From 2003 to 2014, the assigned ICD9‐RDS diagnosis, and utilization of NIMV increased and mortality among infants assigned the ICD9‐RDS diagnosis decreased. With higher survival, hospital cost increased incrementally, indicating the importance of ongoing analysis of appropriate reimbursement for the care provided at tertiary centers for preterm infants.